Determinants of Insecticide-treated Net use among Pregnant Women with Malaria in West Papua, Indonesia - Tita Husnita Madjid; KI Mantilidewi; H Susiarno; Ari Irawan Romulya (Universitas Andalas, 2022)
Introduction: Malaria in pregnancy is still a major cause of neonatal adverse outcome in West Papua, Indonesia. In accordance to the recommendation of the World Health Organization, local government have attempted to prevent malaria in pregnant women by distributing insecticide-treated nets (ITNs). Objective: This study aimed to assess the pattern of malaria infection and the use of ITNs among pregnant women in the city of Manokwari, West Papua, Indonesia.Methods: We recorded all pregnant women who were admitted to the Manokwari District Hospital during May 2017 to April 2018 with malaria. From a total of 335 cases, 125 women agreed to be interviewed on their ITN use at home.Results : Out of a total of 335 cases during the enrolment period, 175 (52%) were found to be infected with Plasmodium falciparum. Chief complaints were fever (28.8%), hyperemesis (25.6%); cephalgia (18.4%); anaemia (15.2%); preterm labor (8.8%) and diarrhoea (3.2%). Only 23.2% of the 125 samples used ITN at home. Most did not have access government-distributed free nets (43.8%); others did not use it due to the foul smell of the nets (17.7%); the heat experienced when sleeping under nets (29.1%); and fear of insecticide side-effect (9.4%). Conclusion: There is suboptimal use of ITN as a preventive measure against malaria in pregnancy in Manokwari, West Papua. Better distribution and other alternative to physical barriers should be considered by the governmentKeywords: Malaria, pregnancy, insecticide-treated net